A COMPUTATIONAL AND EXPERIMENTAL INVESTIGATION OF AIR FLOW AND CONTAMINANTS CONCENTRATION IN A LABORATORY WITH MIXING VENTILATION SYSTEM - Ala'a A. Mahdi; Mohammed W. Khadim; Ammar A. Mohammed Hassn (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ, 2018)
In this research an experimental and computational analysis under Iraqi climate of temperature distribution, velocity and contaminants concentration in the air-conditioned laboratory have been studied for two case studies. Case-I chosen internal combustion engine laboratory of dimensions (10.3 x 8.7 x 3.75) m with a different number of engines used in the experiments and Case-II chosen laboratory of chemical and petroleum products dimensions (3.7x3.6x3.3)m with different locations of the supply air terminal diffuser compared to the existing design situation. ANSYS FLUENT 14 used to simulate the model's laboratories for compared between the present practical work and numerical work results which are acquired by using RNG K-ε and SST k-ω models and found that the SST k-ω model more accurate. The SST (k-w) turbulence model were employed to solve the governing equations numerically with Reynold number 28,933 and validated by comparing the numerical results with experimental data, and this comparison gives a good agreement. The numerical results for case-I compared with experimental data, while for case-II, the numerical results compared with the standard value due to Iraqi cooling code and ASHRAE standards. The results showed that the mixing ventilation system is able to remove various types of pollutants effectively up to 90% in addition to providing human thermal comfort conditions with the effectively of heat removal up to 85% for the state of the internal combustion laboratory. The second case at laboratory of chemical and petroleum products when the supply air terminal diffuser in the same side, the results showed an increase in comfort conditions by up to 40%.Lastly, from the research, it was found that the pollutant transportation and distribution depend in general upon several factors such as type and location of contaminant source, building geometry, the arrangement of air terminal diffuser opening, and thermal/fluid boundary conditions for example flow rate. Numerical simulation of the velocity and diffusion fields in a conventional flow in laboratories is very useful in comprehending flow and diffusion patterns within different changes of the flow conditions.